VISUALISASI KARYA SENI BATIK KAWENTAR YANG BERBASIS KARYA SENI MODERN ART DAN KEARIFAN LOKAL DI GARUT - Pandanwangi, Ariesa; Sukapura Dewi, Belinda; Purnomo Adi, Sigit (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Kawentar Batik draws inspiration from the works of world-renowned painters such as Picasso, Piet Mondrian, Miró and Franz Klein. This is an effort to increase marketing reach, but few works by these artists have been adopted into batik artworks to inspire innovation. Kawentar batik is the first to do so. This study addresses the question of how modern art is implemented in Garut batik. This study uses a qualitative descriptive method. Feldman's theory is used to analyse the work; this method consists of four stages: description, formal analysis, interpretation, and assessment. The research sample comprises two batik writings in a modern art style. The results of the study show that batik combines local values with the main subject of modern art. The colours of the batik are influenced by those of the paintings, namely the colours used by modern artists. This study concludes that Kawentar batik draws inspiration from the works of renowned artists from around the world.